An abnormal lymphatic phenotype is associated with subcutaneous adipose tissue deposits in Dercum’s disease - Rasmussen, John C. (2014)
OBJECTIVE: Investigational, near-infrared fluorescence (NIRF) lymphatic imaging was used to assess lymphatic architecture and contractile function in participants diagnosed with Dercum’s disease, a rare, poorly understood disorder characterized by painful lipomas in subcutaneous adipose tissues. DESIGN AND METHODS: After informed consent and as part of an FDA-approved feasibility study to evaluate lymphatics in diseases in which their contribution has been implicated, three women diagnosed with Dercum’s disease and four control subjects were imaged. Each participant received multiple intradermal and subcutaneous injections of indocyanine green (ICG, total dose ≤400µg) in arms, legs, and/or trunk. Immediately after injection, ICG was taken up by the lymphatics and NIRF imaging was conducted. RESULTS: The lymphatics in the participants with Dercum’s disease were intact and dilated, yet sluggishly propelled lymph when compared to control lymphatics. Palpation of regions containing fluorescent lymphatic pathways revealed tender, fibrotic, tubular structures within the subcutaneous adipose tissue that were associated with painful nodules, and, in some cases, masses of fluorescent tissue indicating that some lipomas may represent tertiary lymphoid tissues. CONCLUSIONS: These data support the hypothesis that Dercum’s disease may be a lymphovascular disorder and suggest a possible association between abnormal adipose tissue deposition and abnormal lymphatic structure and function.